A review on the characterisation and processing of oolitic iron ores. (September 2018) - Quast, Keith
Highlights: Oolitic iron ores comprise a significant and unique mineral assemblage. The nature of oolitic iron ores can predispose them to contain high levels of impurities. Processing can vary from simple to complex involving reduction roasting and magnetic separation. Most processing routes involve removal of phosphorus to allow subsequent iron and steel making. Abstract: Oolitic iron ores are a distinctive subset of iron ore deposits, and are characterised by their spherical grains composed of concentric layers containing hematite and goethite along with impurity elements such as silicon and phosphorus. Depending on their petrology, oolitic iron ores may require very simple or extremely complex flowsheets for their processing. This review focussed on beneficiation by conventional mineral processing techniques and also more energy intensive processes involving heating (roasting) or leaching. The aim of roasting is to transform minerals like hematite and goethite to magnetite or metallic iron, making them amenable to concentration by magnetic separation. The overall aim of this review was to highlight possible techniques for economically processing oolitic iron ores for the subsequent production of iron and steel. An attempt has been made in assembling this review to strike a balance between more historical documentation and a plethora of recent information readily obtainable by searching electronic data bases.